Znaczenie gospodarcze private equity/venture capital dla emerging markets (przykład Polski) - Jabłoński, Sebastian; Waszkiewicz, Maciej (Economical Drift of Private/Venture Capital in the Emerging Markets, 2007)
The purpose of this publication is to highlight the important factors in the process of the economical development of Poland in the sector of Private Equity/Venture Capital. In order to accomplish the aforementioned objectives, the analysis has been undertaken based on the statistical data of EVCA, PriceWaterHauseCoopers between the years 2000 and 2005. The above data from PWC has been an immense source of knowledge to reflect changes that have taken place in this investment world of the capital market. In summary, the article has described the functionality barriers of the Private Equity/Venture Capital market in Poland and has indicated important factors on further growth of this segment in Poland. Furthermore, very important source of knowledge for this article has come from the website of the Polish Private Equity Association (PSIK), which is one of the most important treasuries, providing in depth knowledge about the Private Equity/Venture Capital. Furthermore, the authors have conducted and researched a series of publications and available reports that have been published recently on the market. The authors believe that the enclosed paper will be treated as a small contribution in analyzing and researching the information on the growing role of the Private Equity/Venture Capital in Poland
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 145-164